2008
DOI: 10.1177/1049732308318031
|View full text |Cite
|
Sign up to set email alerts
|

Certified Nurse Assistants Making Meaning of Direct Care

Abstract: Using qualitative data from 87 focus groups with CNAs in 16 nursing homes in Massachusetts, this study explores ways CNAs make meaning of their work despite devaluations such as lack of respect from management and residents, and the physical and emotional demands of such low status work. CNAs' meaning-making represents an effort to assert a positive identity rather than accept the stigmatization associated with their work. Assertions of the value help CNAs reconstitute their identities. Assertions of meaning, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 16 publications
2
36
0
4
Order By: Relevance
“…Dieselbe Studie zeigt, dass Pflegehelfende mit mangelndem Respekt des Managements, Exklusion von Entscheidungen und der Kommunikation der Organisation, einer hohen Arbeitslast und einem geringen Gehalt konfrontiert sind [7][8][9]. In den USA, in Deutschland und in der Schweiz werden die verschiedenen Arbeitsbelastungsfaktoren u. a. für die hohen Fluktuationsraten in den Pflegeberufen verantwortlich gemacht [5,7,10].…”
Section: Arbeitsbelastungunclassified
See 2 more Smart Citations
“…Dieselbe Studie zeigt, dass Pflegehelfende mit mangelndem Respekt des Managements, Exklusion von Entscheidungen und der Kommunikation der Organisation, einer hohen Arbeitslast und einem geringen Gehalt konfrontiert sind [7][8][9]. In den USA, in Deutschland und in der Schweiz werden die verschiedenen Arbeitsbelastungsfaktoren u. a. für die hohen Fluktuationsraten in den Pflegeberufen verantwortlich gemacht [5,7,10].…”
Section: Arbeitsbelastungunclassified
“…Wichtige Aufgaben übernehmen die Pflegehelfenden auch in der Kommunikation mit den Bewohnerinnen und Bewohnern sowie in der Informationsüber-mittlung. Das Pflegefachpersonal trägt die übergeordnete Verantwortung über diese an die Pflegehelfenden delegierten Arbeiten [8].…”
Section: Arbeitsbelastungunclassified
See 1 more Smart Citation
“…The care worker is usually a woman, sometimes a migrant worker, holding an ill-paid job, with little social status, and moreover one that is often stigmatized because of the dirty work it involves. Even her employer tends to devalue her contribution (Pfefferie and Weinberg 2008). Patients and clients have the power to 'act up', to refuse treatment or care, or to make it difficult for the worker to perform.…”
Section: The Power Relations Of Body Workmentioning
confidence: 99%
“…Pfefferle and Weinberg (2008) found that direct care workers in nursing homes experienced stress at work that might have contributed to turnover through factors such as low job satisfaction. Castle, Engberg, Anderson, and Men (2007) found job satisfaction to be predictive of actual turnover after 1 year of employment.…”
Section: Introductionmentioning
confidence: 98%